Comparison Of Central Aspect of Teacher-Centered and Learner-Centered Pedagogical Models - Mahliyo Kukiboyeva (Indonesian Journal Publisher, 2024)
This article compares teacher-centered and learner-centered approaches to instruction by examining their philosophical foundations, pedagogical practices, strengths, and limitations. Teacher-centered models, grounded in behaviorist and direct instruction traditions, emphasize clarity, efficiency, and the teacher’s role as transmitter of knowledge. Learner-centered approaches, rooted in constructivist, socio-cultural, and humanistic theories, prioritize student agency, inquiry, and reflective engagement. Drawing on seminal theorists such as Dewey, Vygotsky, Rogers, and Freire, as well as empirical syntheses by Rosenshine, Hattie, Black and Wiliam, and Cornelius-White, the article evaluates evidence for each approach in terms of cognitive, affective, and equity outcomes. Findings indicate that teacher-centered strategies are effective for introducing foundational knowledge, while learner-centered methods promote deeper understanding, motivation, and metacognition when adequately scaffolded